Crystal structure of ipratropium bromide monohydrate, C20H30NO3Br(H2O). Issue 1 (March 2020) - Bhaskar, Shivang; Golab, Joseph T.; Kaduk, James A.; Gindhart, Amy M.; Blanton, Thomas N.
Abstract : The crystal structure of ipratropium bromide monohydrate has been solved and refined using synchrotron X-ray powder diffraction data and optimized using density functional techniques. Ipratropium bromide monohydrate crystallizes in the space group P 21 / c (#14) with a = 8.21420(7) Å, b = 10.54617(13) Å, c = 24.0761(39) Å, β = 99.9063(7) °, V = 2054.574(22) Å 3, and Z = 4. Both hydrogen atoms of the water molecule act as donors to the bromide cation, forming a ring with the graph set R 2, 4(8). The hydroxyl group also acts as a donor to Br. Several C–H⋯Br hydrogen bonds are present. The water molecule acts as an acceptor in two C–H⋯O hydrogen bonds from methyl groups. The ketone acts as an acceptor in C–H⋯O hydrogen bonds from methyl groups, a methylene group, and a methyne group. The hydroxyl group acts as an acceptor in a C–H⋯O hydrogen bond from a phenyl carbon atom. The powder pattern is included in the Powder Diffraction File™ as entry 00-066-1611.